2020
DOI: 10.1002/ejoc.202001425
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to N‐Tf 2‐Aryl‐2,3‐Dihydroquinolin‐ 4(1H)‐ones via a Ligand‐Free Pd(II)‐Catalyzed Oxidative Aza‐Michael Cyclization

Abstract: Figure 1. Examples of biologically active 2-aryl-2,3-dihydroquinolin-4(1H)ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, we reported that chromanones, simple ketones, can be converted into flavones and flavanones via palladium( ii )-catalyzed dehydrogenation-mediated coupling sequences with arylboronic esters and acids, respectively, and also recently reported that N -substituted azaflavanone can be synthesized from N -substituted aminodihydrochalcones via Pd( ii )-catalyzed oxidative cyclization. 16 Inspired by these previous works, we sought to find novel and divergent synthetic routes to a variety of privileged flavonoids, particularly flavones and flavanones using common starting materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we reported that chromanones, simple ketones, can be converted into flavones and flavanones via palladium( ii )-catalyzed dehydrogenation-mediated coupling sequences with arylboronic esters and acids, respectively, and also recently reported that N -substituted azaflavanone can be synthesized from N -substituted aminodihydrochalcones via Pd( ii )-catalyzed oxidative cyclization. 16 Inspired by these previous works, we sought to find novel and divergent synthetic routes to a variety of privileged flavonoids, particularly flavones and flavanones using common starting materials.…”
mentioning
confidence: 99%
“…First, Pd( ii )-catalyzed dehydrogenation may result in the oxidative conversion of 2′-hydroxydihydrochalcone 1a into 2′-hydroxychalcone 2a. 16 Then, common intermediate 2a can be transformed into the desired flavanone 4a through Michael addition and flavone 3a through oxidative Heck coupling, respectively, depending on the optimized reaction conditions that are used in the synthesis. During oxidation processes such as dehydrogenation and oxidative cyclization, Pd(0) species regenerated in the reaction would be reoxidized into Pd( ii ) via the [O] process, where O 2 or Cu(OAc) 2 acts as the main oxidant.…”
mentioning
confidence: 99%